Optimization of synthesized nano cu-based catalyst to enhance biodiesel production - Arvyvie Abie Jamil (2016)
Nowadays, the productions of biodiesel from renewable sources such as palm oil have been extensively studied due to the depletion of fossil fuel. The difficulties during the separation and purification of the homogeneous catalyst used in the production of biodiesel product led to the development of a heterogeneous catalyst. In this study, heterogeneous Cu-based catalyst was successfully synthesized using impregnation associated with sonochemical method. Two types of catalysts support (A1203 and MgO) were optimized and activated under two different activation conditions (air and nitrogen). Four parameters were optimized which are i) sonication time, ii) activation procedure (time and gas), iii) catalyst support (Al₂O₅ and MgO) and iv) metal loading (5 to 20 wt. %). Throughout the characterization data, it was confirmed that the optimized activation condition was at 90 minutes sonication time either 3 hours under nitrogen activation condition or 4 hours under air activation condition. From the XRD analysis, it was revealed the formation of CuO phase under air condition (20CuAA(4h)) produced smaller average crystal size of 23.6 nm compared to Cu phase produced under nitrogen condition (20CuAN(3h)), 30.1 nm. Moreover, effect of catalyst support has confirmed the MgO catalyst (10CuMA) produced highly dispersed of CuO phase with an average crystal size smaller than Ah03 catalyst (10CuAA), 8.5 and 24.7 nm respectively. FESEM and TEM analysis also confirmed the MgO catalyst (10CuMA) produces small CuO nanocatalyst with lamella-like structure. The selected catalyst (5 to 20 wt. % of CuO/MgO catalyst) was performed under the transesterification reaction with a fixed parameter: 1 % w/w catalyst, temperature (65°C), molar ratio of methanol to oil (10:1) and 6 hours reaction time. Throughout the study, 10 wt. % of CuO/MgO catalyst (10CuMA) showed a high catalytic activity with high conversion and high selectivity of palmitic acid, 97.2 % and 51.5 % respectively. From the XRD analysis, it was observed an average crystal size of CuO for 10CuMA catalyst was 8.5 nm. While from the BET analysis, it showed the 10CuMA catalysts is a mesoporous nanocatalyst (133.9 cm³ g⁻¹) with an average pore diameter is less than 5 nm. FESEM and TEM analysis observed the 10CuMA catalyst consist of nanoparticles with lamella-like structure. From the thermal analysis, it was determined the 10CuMA catalyst consists of three stages of thermal decomposition with 29.4 % of weight loss and 70.6 % of ash residue. Overall the biodiesel produced by the 10CuMA catalyst meet the requirement of EN14214 standards with the acid value of less than 0.5 mg' KOH g-l and low iodine value.